PENGARUH KEGIATAN EXTRA FEEDING DAN POLA ASUH ORANGTUA TERHADAP KEMANDIRIAN ANAK - TASU’AH, NENENG (JPUD - Jurnal Pendidikan Usia Dini, 2013)
The aims of this research was to understand comprehensively the influence of extra feeding activities and parenting toward independence children (Experiment in student class I at SDN Pejaten Barat, South Jakarta, 2013). The method usedin this studyis the experimental method with Children independen ceas the main problem which is the dependent variable. While first independent variableis the Extra Feeding activity (in this study is Cooking Fun activities and activities Role Playing) and the second independent variable is the parenting parent (in this study is the pattern of otoritarian parenting, democratic and permissive). In this study the sampling techniqueto be used the multi stage cluster sampling. The sample In this study is in two elementary school SDN 12 and SDN Pejaten Barat 10 each class I have a number of students of approximately 30 students so that a total number of 60 students, but at the time of the study the researchers only select students based on parenting question naire results by category otoritarian parenting, permissive, democratic and 10 students respectively so that the samplein this study were 30 students as control class in SDN Pejaten Barat 10 and 30 students as an experimental class at SDN Pejaten Barat 12. This study is a design experiment with designs fatorial 2x3. Therefore, data analysis using ANOVA two lines, iftested the difference, followed by Tukey’s testor Scheffe testto determine which one is higher. The finding lead to the recommendation to use extra feeding activities and parenting to improving independence children. And teacher should be free to use learning methods especially extra feeding activities. Keyword: extra feeding activities, parenting, and independence children Penelitian ini bertujuan untuk memahami secara komprehensif pengaruh kegiatan extra feeding dan pola asuh terhadap kemandirian anak di SDN Pejaten Barat, Jakarta Selatan, 201. Variabel independen pertama adalah aktivitas extra feeding (kegiatan Fun cooking dan kegiatan Role Playing) dan variabel independen kedua adalah pola asuh orang tua (pola asuh otoritarian, demokratis dan permisif). Sampel penelitian adalah SDN 12 dan SDN Pejaten Barat 10, masingmasing kelas I memiliki jumlah siswa sekitar 30 siswa sehingga jumlah total 60 siswa, peneliti memilih siswa berdasarkan hasil pengasuhan berdasarkan kategori pola asuh otoritarian, permisif, demokratis dan masing-masing 10 siswa sehingga sampel penelitian ini adalah 30 siswa sebagai kelas kontrol di SDN Pejaten Barat 10 dan 30 siswa sebagai kelas eksperimen di SDN Pejaten Barat 12. Penelitian ini menggunakan eksperimen dengan desain penelitian 2x3 fatorial. Oleh karena itu, analisis data menggunakan ANOVA dua jalur, uji perbedaan, diikuti oleh test Tukey Scheffe testto untuk menentukan mana yang lebih tinggi. Temuan menyebabkan rekomendasi untuk menggunakan kegiatan extra feeding dan pengasuhan anak-anak untuk meningkatkan kemandirian. Guru harus bebas untuk menggunakan metode pembelajaran kegiatan makan terutama extra feeding. Kata Kunci: aktivitas extra feeding, pola asuh orang tua, dan kemandirian anak